Population Densities of Faunus ater and Terebralia sulcata in Areas Affected by Nickel Mining Overburden and Reference Site in the Mangrove Ecosystem of Pomalaa, Southeast Sulawesi - Slamet Budi Prayitno; Max Rudolf Muskananfola; Suryanti Suryanti; Muhammad Fajar Purnama (Institut Pertanian Bogor, 2025)
The Pomalaa mangrove ecosystem in Southeast Sulawesi primarily consists of the gastropods Faunus ater and Terebralia sulcata. The Pomalaa District is the largest nickel mining area in the region, and mining activities have significantly impacted the ecosystem by introducing overburdened sediment waste, visibly affecting the substrate, roots, and stems of mangroves. This research was conducted from June to September 2023 in the mangrove ecosystem of the Pomalaa District. This study examined the density differences of gastropods F. ater and T. sulcata in areas impacted by nickel mining overburden compared to minimally disturbed sites in the Pomalaa mangrove ecosystem, Southeast Sulawesi. Sampling was conducted using purposive and simple random sampling techniques. Gastropod samples were obtained (counted), analyzed for density, and associated with mangrove density in the sampled area. The results showed that the highest densities of F. ater and T. sulcata were found in areas not affected by nickel mining overburden (reference sites) with ranges of 50-153 ind./m2 and 24-57 ind./m2, respectively. In contrast, in the areas affected by overburden, the population densities of the two types of gastropods ranged from 0-11 ind./m2 for T. sulcata and to 0-21 ind./m2 for F. ater) despite having high mangrove densities in several places. The distribution pattern of these two species was in the clumped category. This study found a significant decrease in the density of two typical mangrove slug species in overburden-affected areas compared to the reference sites. Keywords: gastropod, mangrove, overburden, nickel mining, species density